2012
DOI: 10.1152/ajpheart.00231.2012
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II enhances AT1-Nox1 binding and stimulates arterial smooth muscle cell migration and proliferation through AT1, Nox1, and interleukin-18

Abstract: The redox-sensitive transcription factors NF-κB and activator protein-1 (AP-1) are critical mediators of ANG II signaling. The promitogenic and promigratory factor interleukin (IL)-18 is an NF-κB- and AP-1-responsive gene. Therefore, we investigated whether ANG II-mediated smooth muscle cell (SMC) migration and proliferation involve IL-18. ANG II induced rat carotid artery SMC migration and proliferation and IL-18 and metalloproteinase (MMP)-9 expression via ANG II type 1 (AT(1)) receptor. ANG II-induced super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
90
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 51 publications
2
90
0
Order By: Relevance
“…25,35) Also, angiotensin II can induce NADPH oxidase 1 expression and increase ROS production in VSMCs. [36][37][38] In this study, we found that naringenin could significantly decrease the level of ROS production in angiotensin II-treated VSMCs in vitro and the serum level of 8-iso-PGF2α, an oxidative stress marker, in balloon injured rats. Since NADPH oxidase and SOD are important enzymes in regulation of ROS production and degradation, respectively, 39,40) we further investigated whether naringenin could change the activities of NADPH oxidase and SOD.…”
Section: Discussionmentioning
confidence: 57%
“…25,35) Also, angiotensin II can induce NADPH oxidase 1 expression and increase ROS production in VSMCs. [36][37][38] In this study, we found that naringenin could significantly decrease the level of ROS production in angiotensin II-treated VSMCs in vitro and the serum level of 8-iso-PGF2α, an oxidative stress marker, in balloon injured rats. Since NADPH oxidase and SOD are important enzymes in regulation of ROS production and degradation, respectively, 39,40) we further investigated whether naringenin could change the activities of NADPH oxidase and SOD.…”
Section: Discussionmentioning
confidence: 57%
“…46,47 Angiotensin II induces upregulation of Nox1. 48 Therefore, it has been postulated that Nox1 could play an important role in the development and progression of diabetic nephropathy. 44,45 However, in our study, Nox1 deletion was not associated with an improvement in diabetes-related renal injury.…”
Section: Discussionmentioning
confidence: 99%
“…45 In the balloon injury model in rats a recent report has described a role for Nox1 involving the direct binding of this enzyme to the AT1 receptor. 46 In STZ-diabetes mellitus, activation of Nox1 but not Nox4 or Nox2 has been implicated in eNOS uncoupling and endothelial dysfunction, although these studies were performed in a nonatherosclerosis prone mouse model. 44 The role of Nox1 in atherosclerosis has not been extensively explored.…”
Section: Discussionmentioning
confidence: 99%